AKSESIBILITAS TERHADAP UTILISASI FASILITAS LAYANAN KESEHATAN DASAR DI PROVINSI PAPUA (RISKESDAS 2013) - Efraim Mudumi; Mubasysyir Hasanbasri; Lutfan Lazuardi (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: Access to basic health services is a human rightin the health sector achieve social justice for all Indonesianpeople. Access to health care facilities in Papua remains a realchallenge for the government, especially if it is associated withthe goal to improve the health status, reduce morbidity andmortality. The difficulty of access to health facilities led todisparities in health status between regions in Indonesia.Objective: Analysis patterns utilization of health facilities andthe factors that access barriers to health centers in the provinceof Papua.Methods: Analysis of secondary data comes from a survey ofbasic health research in 2013 with the kind of cross-sectionalstudies.Results: Of the 4562 respondents as many as 3152 (69,09%)utilize health centers. Probability better utilization of healthcenters on the rich than the poor (OR = 4,17, 95% CI = 3,23-5,38). Participants private health insurance and social securityare more likely to utilize health centers (OR = 5,87, 95% CI =2,82-12,23). Living in the urban area increasing the utilization ofhealth centers compared with rural area (OR = 1,24, 95% CI =0,98-1,56). Probability health centers utilization in swamplandbetter than others (OR = 2,17, 95% CI = 1,36- 3,45). Time travelless than 30 minutes are more likely to utilize health centerscompared with a travel time more than 30 minutes (OR = 1,28,CI = 1,14-2,17). Motor vehicles are more likely to utilize healthcenters (OR = 3,00, CI = 2,36 to 3,81). Transportation costs ofmore than IDR100.000 is more likely to take advantage of healthcenter (OR = 2,59, 95% CI = 1,59-4,2). Conclusion: The availability of health facilities, travel time,transport costs and the availability of transportation still bebarriers of accessibility. Utilization patterns varied types of basichealth facilities, primary health centers are the types of facilitiesthat the most widely used. There is inequity between the poorand rich in the utilization of basic health services.